Decoupled Stability of Above‐ and Belowground Productivity Across Global Change Drivers - Ze Zhang; Hongyan Liu; Zidong Li; Boyi Liang; Jinghua Qi; Jiamei Li; Yann Hautier (Global Change Biology, 2026)
Grassland ecosystems play essential roles in global carbon cycling and biodiversity conservation, yet it remains unclear whether belowground productivity is less sensitive to environmental change than aboveground productivity. Previous studies have predominantly focused on aboveground net primary productivity (ANPP) stability, potentially overestimating ecosystem vulnerability by neglecting critical belowground processes. By synthesizing 1513 observations from 113 studies across 85 grassland ecosystems worldwide, we quantified the responses of productivity, temporal stability, and carbon allocation to nine global change drivers, including nutrient enrichment, altered precipitation, elevated CO 2 , warming, mowing, and grazing. Our results reveal that belowground net primary productivity (BNPP) stability shows generally weaker responses to global change drivers than ANPP stability. In addition, variation in ANPP stability was most closely associated with broad‐scale climatic indices of water supply (precipitation and aridity, used here as proxies for plant‐available soil water), whereas BNPP stability was more closely associated with edaphic context (soil moisture‐related and fertility‐related properties). These distinct patterns suggest that broad‐scale climatic variability is more strongly reflected in aboveground stability, whereas belowground stability is better captured by edaphic predictors related to water retention and nutrient availability. Moreover, variation in belowground carbon allocation was consistently associated with stronger coordination between above‐ and belowground responses and with the maintenance of BNPP stability under global‐change perturbations, suggesting a potential allocation‐related pathway linked to ecosystem resistance. Our findings challenge traditional ecological theories emphasizing unified above‐belowground responses and suggest that previous research focusing solely on aboveground processes may have overestimated grassland vulnerability. This synthesis provides critical insights for predicting grassland ecosystem stability and functioning under ongoing global environmental changes.